Occult HBV infection among a cohort of Nigerian adults (2009)
"OBJECTIVE:To determine markers of HBV infection and detect the presence of its occult infection in serum of a cohort of adult Nigerians. METHODOLOGY:The study involved 28 adult Nigerians with viral hepatitis (Group 1) and 28 apparently healthy adult Nigerians as controls (Group 2). Their sera were assayed for HBsAg, HBeAg, anti-HBe, anti-HBc, anti-HBs, and anti-HCV, while HBV DNA was determined in 15 patients with chronic hepatitis. Significance of differences between the patients and control subjects was assessed using Chi-square test at a 95% confidence level. RESULTS:Sero-detection of HBsAg, HBeAg, anti-HBe and anti-HBc was higher among the patients compared to the controls. HBV infection was diagnosed by HBsAg (89%) and a duo of HBsAg and anti-HBc (100%) among the patients. Similarly, eleven and four types of different patterns of HBV markers were observed among the respective groups. Anti-HBe (9.5%), anti-HBc (14.3%), and anti-HBs (9.5%) were detected among all the subjects who were sero-negative for HBsAg. HBV DNA was also detected in 86.7% of the 15 patients with chronic hepatitis, while occult HBV infection was observed in 7.2% of the patients and none (0%) of the controls, p < 0.05. Furthermore, HCV infection occurred among subjects with all the different patterns of HBV markers, except those with occult HBV infection and natural immunity to HBV. CONCLUSION:This study shows that occult HBV infection is present among Nigerian adults and determination of HBsAg, anti-HBc, anti-HBe, and HBV DNA will assist in its detection."